Estimation of Artemether and Arteether by High Performance Thin Layer Chromatography - P. AGARWAL, SURAJ; ALI, ASGAR; AHUJA, SHIPRA (Asian Journal of Chemistry, 2010)
A new, simple, accurate and precise high performance thin layer chromatographic method has been developed for the estimation of artemether and arteether as pure drug powder and in pharmaceutical formulations. The method employs silica gel F254 as stationary phase on aluminium foil and mobile phase comprising toluene: butanol (10:1) in case of artemether and toluene: dichloromethane (0.5:10) for arteether. Since artemisinin derivatives are non-UV absorbing compounds, they were converted into UV absorbing derivative using a derivatizing agent. A solution of 10 % v/v sulphuric acid in ethanol gave prominent well-resolved blue coloured spot for artemether and vanillin in sulphuric acid in ethanolic solution gave prominent well-resolved pink coloured spot for arteether. In both cases, the spots were stable for more than a day. The densitometric analysis of both the drugs was carried out in the absorbance mode at 546 nm. The Rf values were 0.45 for artemether and 0.30 for arteether. The linear detector response was observed between 100-600 ng per spot for artemether and arteether and the calibration plots showed good linear relationship with coefficient of correlation, r = 0.9981 and 0.9989, respectively, with respect to peak area. The methods were validated for precision, recovery and robustness. The limits of detection and quantitation were 25 and 28 ng/spot for artemether and 75 and 84 ng/spot for arteether, respectively. The recovery study was carried out by standard addition method. The recovery was found to be 99.49 ± 0.687 for artemether and 99.50 ± 0.590 for arteether.